Size of Snake Eyes Correlates With Habitat Types and Diel Activity Patterns - Huang, Mason Chen-Wei; Liao, Chen-Pan; Chou, Chun-Chia; Lin, Jhan-Wei; Huang, Wen-San (Frontiers in Ecology and Evolution, 2022)
Eye size determines the resolution and light sensitivity of visual functions and is a result of vertebrate adaptation to the environment. The habitats of snake species are diverse, ranging from fossorial, terrestrial, arboreal, to aquatic; they also demonstrate a variety of behavioral and physiological characteristics, such as activity time, feeding patterns, and prey detection. In this study, we comparatively investigated how the relative eye size (i.e., eye diameter versus head width) associated with the ecological (i.e., habitat), behavioral (i.e., diel activity pattern, foraging strategy), and physiological traits (i.e., the presence of pits) respectively across six snake families. Among the traits we examined, we found that terrestrial and/or diurnal snakes tended to exhibit the larger relative eye size, indicating the evolutionary responses of eye size to changes in habitat types and activity patterns respectively, while no evidence of how foraging strategies and the presence of pits affected snake eye size was found. Our findings not only shed light on the adaptive significance of the visual system in diversifying the behaviors and the environments exploited in snakes, but also underline the interactive effects of multidimensional evolutionary attributes (e.g., behavior, ecology, physiology and phylogeny) on the evolution of optimal visual performance.